PENINGKATAN PRESTASI BELAJAR SISWA SLB NEGERI KOTA LANGSA MELALUI APLIKASI SELF PRO - Desi Sinamo, Yemima; Evanita Lubis, Dian; Chairiyah Jambak, Maulidina; Ayu Lestari, Putri; Arico, Zulfan (Fakultas Teknik, Universitas Samudra, 2024)
Langsa City State Special School (SLB) is one of the SLBs in Langsa City. Langsa State SLB has a total of 244 students, with 64 people with physical disabilities, 34 people with visual impairments, 53 people with hearing impairments, 64 people with mental disorders and 29 people with mental physical disorders. Langsa City State Special School has a problem, namely the lack of student interest in learning activities, in 2023 students tend to feel bored and not focused in the process of receiving knowledge from teachers. Based on the needs assessment from the results of interviews with teachers, an understanding of the importance of understanding digitalization technology in the learning process is needed, especially through mentoring who knows the concepts and development of children with special needs. Based on 10 indicators of achievement of output targets, PKM-PM activities have reached 99%. Activities that have not been fully achieved are the final report which is still 10% in progress. From the results of the PKM-PM activity entitled